The Effectiveness West Java Future Leaders (Millennial Adjutant) Program for Bureaucratic Reform - Dinda Rosanti Salsa Bela; Suswanta Suswanta (Journal of Governance, 2022)
The purpose of this study was to assess the effectiveness of the Millennial Adjutant Program of West Java Future Leaders in creating a superior younger generation. This study uses Q-DAS (Qualitative Data Analysis Software) and Nvivo 12 plus to provide an exploration and description of the Millennial Adjutant Program West Java Future Leaders. The results of this study are the effectiveness of the West Java Future Leaders program in this study as seen from several indicators, namely the program's success, the success of the target, and the level of output and input. The success of the West Java Future Leaders program can be seen based on the enthusiasm of the participants, which increases every year. The target of this program is young people throughout Indonesia, who are expected to create a superior young generation to meet the road map of bureaucratic reform.